Studying of Some Physiological Parameters in Patients with Inflammatory Bowel Disease ( IBD ) in Al-Anbar Province - Thikra Majid Muhammed AL-Obaidy; Hasan Ali Mutar; Thaer Abdulqader Salih (Indian Journal of Forensic Medicine & Toxicology, 2022)
This study was carried out to determine some hematological, parameters in patients with IBD. the total number were 100 blood samples, 60 samples from patients with IBD (cases), while the remaining 40 samples from persons without IBD (control), Ages ranged from 15 to 60 years. who attended general teaching hospital in Ramadi city in Al-Anbar governorate. a comparison in hematological parameters was carried between the two groups with each other showed that there was significant difference between patients and control with (p<0.05). and the means levels for hemoglobin HB (10.09 g/dl), (13.18 g/dl) \ there was significant difference between patients and control with (p<0.05). and the means levels for red blood cells RBC (3.194 X 106 c/ mm3), (5.291X 106 c/ mm3) \ there was significant difference between patients and control with (p<0.05). and the means levels for white blood cells WBC (12.39X 103 c/ mm3), (7.300X 103 c/ mm3) there was significant difference between patients and control with (p<0.05). and the means levels for \platelet (561.2X 103 c/ mm3), (258.4X 103 c/ mm3).